Dynamics of different types of post-traumatic regeneration of the lower jaw bone tissue based on X-ray data - Masna , Z.Z.; Chelpanova , I.V.; Ambarova , N.O.; Masna-Chala , O.Z.; Chalyi , I.T. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. Nowadays, in the field of surgical dentistry, osteoplastic materials are widely used to fill bone defects after bone-destroying injuries and tooth extractions, in order to preserve the volume and quality of the bone tissue of the alveolar bone tissue. The aim of our research was to compare the dynamics of bone tissue regeneration of the rabbit's lower jaw and the restoration of its quality after inflicting a bone-destroying injury and using different methods of its correction. Methods. Research was done on 20 adult 6–7-month-old rabbits, having 2.5-3 kg weight, which were segregated into control and two experimental groups of 5 rabbits. Another 5 intact animals were examined to determine normal bone density in the area of ​​injury. Animals of the control and experimental groups under combined anesthesia were subjected to bilateral bone-destructive trauma (in the toothless part of the jaw) with a dental drill, that disrupted the integrity of the bone tissue of the alveolar part of the lower jaw, 4 mm deep and 3 mm wide. The control group included animals with a bone tissue defect that healed under a blood clot. The 1st experimental group consists of animals whose bone defect was filled with the bone substitute material CompactBoneB. The 2nd experimental group – animals whose bone defect was filled with a natural matrix for the formation of new bone cells, Collacone from Botiss dental. Monitoring the condition of bone tissue in the area of ​​the applied defect was carried out 7, 14, 21, 28, 35 days after the injury. Densitometric examination of bone tissue was carried out using the VixWin PRO program. Bone tissue density was calculated in arbitrary gray units (AUG). Results. The normal mineral density of the bone tissue of the lower jaw is 71.25+1.02. It was found that the post-traumatic regeneration of bone tissue has a different course depending on the material used to fill the bone defect. During the healing of a bone injury under a blood clot, the dynamics of bone tissue density in the area of ​​the injury for 35 days has a smooth course with a slight increase in indicators compared with norm. When filling defects with osteoplastic materials, we observe expressed dynamics of changes in the investigated indicator with sharp fluctuations at different stages of the experiment (depending on the type of material used). Conclusion. When filling a bone defect with CompactBoneB, a bone substitute material, the mineral density of the bone tissue in the experimental area returns to normal after 35 days following the injury. However, when using Collacone, a natural matrix for the formation of new bone cells, and when healing under a blood clot, the density of the bone tissue in the traumatized area after 35 days of the experiment remains significantly higher than normal values.